DEVELOPING MATHEMATICAL CREATIVE THINKING (CT) ABILITY STUDENTS THROUGH THE TREFFINGER LEARNING MODEL (LM) - Lambertus Lambertus; Mohamad Salam; Rezkiati Rezkiati; Suhar Suhar; Hasnawati Hasnawati (UNIVERSITAS MUHAMMADIYAH METRO, 2023)
The low ability of CT is a problem that occurs in class VIII students of SMPN 1 Kendari. One reason is the application of inappropriate LM. Treffinger's LM is learning by inviting students to think creatively in solving problems based on the facts around them to come up with various ideas and choose solutions. The purpose of this study was to develop the mathematical CT skills of junior high school students. Class VIII SMPN 1 Kendari as a population consists of 9 classes. Class VIII3 and VIII6 were determined by random sampling technique as an experimental class of 26 students and a control class of 25 students. The finding in this study is that students' mathematical CT skills taught by the Treffinger LM are better than in the guided discovery model. Treffinger's LM is superior in developing CT skills. In addition, Treffinger's LM excels in developing aspects of fluency, flexibility, and elaboration of mathematical CT skills. In contrast, the guided discovery LM excels only in developing aspects of originality.Rendahnya kemampuan CT merupakan masalah yang terjadi pada siswa kelas VIII SMPN 1 Kendari. Salah satu penyebabnya adalah penerapan model pembelajaran yang tidak sesuai. Model pembelajaran Treffinger adalah pembelajaran dengan mengajak siswa berpikir kreatif dalam memecahkan masalah berdasarkan fakta-fakta di sekitar mereka untuk memunculkan berbagai ide dan memilih solusi. Tujuan penelitian ini adalah untuk mengembangkan keterampilan CT matematis siswa SMP. Kelas VIII SMPN 1 Kendari sebagai populasi terdiri dari 9 kelas. Kelas VIII3 dan VIII6 ditentukan dengan teknik random sampling sebagai kelas eksperimen sebanyak 26 siswa dan kelas kontrol sebanyak 25 siswa. Temuan dalam penelitian ini adalah kemampuan CT matematis siswa yang diajar dengan model pembelajaran Treffinger lebih baik dibandingkan dengan model penemuan terbimbing. Model pembelajaran Treffinger lebih unggul dalam mengembangkan keterampilan CT. Selain itu, model pembelajaran Treffinger unggul dalam mengembangkan aspek kefasihan, keluwesan, dan elaborasi keterampilan CT matematis. Sebaliknya, model pembelajaran penemuan terbimbing hanya unggul dalam mengembangkan aspek orisinalitas.